PERBEDAAN INTENSITAS NYERI SEBELUM DAN SESUDAH PEMBERIAN METODE ANB (TERAPI PERSALINAN RELAKS, NYAMAN DAN AMAN) PADA INPARTU KALA I FASE AKTIF PERSALINAN DI BPS SITI MUZAYANAH - Triatmi Andri Yanuarini, Triatmi Andri Yanuarini; Ira Titisari, Ira Titisari; Neni Restiana Putri, Neni Restiana Putri (Asuhan Kesehatan : Jurnal Ilmiah Ilmu Kebidanan dan Keperawatan, 2013)
From the data of childbirth reference in Indonesia hospital, to appear all of that is can not endure from this pain. At 2002 in Dr Pringadi hospital Medan for example, the number of childbirth reference who can not endure this pain are 35,7% from 375 childbirth. While of that at 2008 in periode of february in Gambiran hospital Kediri the number of childbirth reference who can not endure this pain are 35% from 51 childbirth.  Anb methode is one of non-farmachologic technique to prevent this pain. This research is aimed to know the different of rain intensity before and after the giving of anb method (relax, comfort and secure theraphy) in childbirth process.Pra-experimental is used as research of design. The sample is mother that facing the childbirth in BPS Siti Muzayanah. It is used consecutive sampling technique. There are 7 person of sample. The data is taken by using observation sheet. The data is analized by using wilcoxon formula with 5 % significance.The result shows t table > t count that 2 > 0, which is mean there is a different of rain intensity before and after the giving of anb method (relax, comfort and secure theraphy) in childbirth process. Hopefully the next study will give more concern about the factors of the pain.Keyword : anb method, pain, inpartu